Genetic alterations of histone lysine methyltransferases and their significance in breast cancer - Liu, Lanxin (Oncotarget, 2014)
Histone lysine methyltransferases (HMTs), a large class of enzymes that catalyze site-specific methylation of lysine residues on histones and other proteins, play critical roles in controlling transcription, chromatin architecture, and cellular differentiation. However, the genomic landscape and clinical significance of HMTs in breast cancer remain poorly characterized. Here, we conducted a meta-analysis of approximately 50 HMTs in breast cancer and identified associations among recurrent copy number alterations, mutations, gene expression, and clinical outcome. We identified 12 HMTs with the highest frequency of genetic alterations, including 8 with high-level amplification, 2 with putative homozygous deletion, and 2 with somatic mutation. Different subtypes of breast cancer have different patterns of copy number and expression for each HMT gene. In addition, chromosome 1q contains four HMTs that are concurrently or independently amplified or overexpressed in breast cancer. Copy number or mRNA expression of several HMTs was significantly associated with basal-like breast cancer and shorter patient survival. Integrative analysis identified 8 HMTs (SETDB1, SMYD3, ASH1L, SMYD2, WHSC1L1, SUV420H1, SETDB2, and KMT2C) that are dysregulated by genetic alterations, classifying them as candidate therapeutic targets. Together, our findings provide a strong foundation for further mechanistic research and therapeutic options using HMTs to treat breast cancer.